Priorities of attention to issues of electronic blackmail on social networking sites - an analytical study of the page (Together against electronic blackmail) - Khudair, Yasmine Khaled (Journal of Tikrit University for Humanities, 2024)
The research was entitled (Priorities of interest in topics of electronic blackmail on social networking sites - an analytical study of the page Together Against Electronic Blackmail), and the aim of the research was to reveal the priorities of interest in topics of electronic blackmail on social networking sites. This research is considered, in terms of type, descriptive research. The researcher relied on the content analysis method to collect, classify and analyze data. The research sample was a comprehensive survey of the posts of the Together Against Electronic Blackmail page on Facebook. The number of posts reached (185), and for the period from 1/1/2023 to 12/1/2023.. The most important results are: 1- The material motives for commercial and economic specializations, in addition to the first among the types, goals, and motives of electronic blackmail, have become the most topical topic among publications. 2- Facebook was one of the most widely used tools for the purposes of electronic blackmail, among other applications. 3- One of the most important methods of electronic blackmail is impersonation on social networking sites. 4- One of the most dangerous and widespread blackmailers and criminals are hackers because of their recent experience in using programs and technologies and exploiting robots in electronic applications.